New table grapes in turkey - Atak A.; Kahraman A.K. (BIO Web of Conferences, 2014)
Table grape consumption is increasing day by day all around the world. New varieties are derived from breeding programs in different countries around the world. Breeding programs in particular are shaped in accordance with the demands of consumers. Especially in recent years, the demands increased for cultivars of table grapes with large berry and maturation at different times, in Turkey as well as in the world market. Also, new cultivars which are tolerant to fungal diseases, late-season and can be stored for a long time had much demand in recent years. For this purpose, new table grapes with these characteristics have been developed by Yalova Atatürk from Central Horticultural Research Institute. Especially in the last few years, the numbers of new cultivars of a total of 12 varieties have been registered. Atak 77, Pembe 77, İsmetbey, Arifbey, Samancı çekirdeksizi, and Yalova Beyazıtable grapes cultivars have been registered in the last few years among the new cultivars. Each one of them is different from the standard cultivars and has been registered with superior properties. Most of these cultivars need less pesticide application in high humidity areas and can be grown successfully. These new cultivars were tested in different ecology and determined suitable regions. These new table grape varieties started to be grown in different part of Turkey nowadays.